Vertical Refractometer for the Monitoring of Main Fermentation - Petr Košin; Jan Šavel; Adam Brož (Kvasný průmysl, 2016)
Fermenting beer samples usually have to be filtered and degased prior to refraction measurement with ordinary horizontal digital refractometer. The article deals with the use of vertical refractometer without the need to treat samples prior to the measurement. The volume of sample (50 ml) is sufficiently low as well as the duration of analysis is (around 1 minute per sample), which enables fast determination of the degree of fermentation needed to control the fermentation. Calculation formulas for the degree of fermentation from the refraction and original wort refraction are summarized.